Investigations on Railway Tracks with Special Emphasis on Partially Unsupported Sleepers Due to Voids - Lammering, R.; Plenge, M. (Engineering Transactions, 2000)
A single sleeper, two adjacent sleepers and a track segment are investigated experimentally in order to get a basic knowledge of the dynamic response of a vertically loaded railway track up to 800 Hz. Since voids are often observed between sleepers and the underlying ballast, special emphasis is laid on investigations of partially unsupported sleepers. Detailed information on the dynamic displacement field is obtained by the holographic interferometry which is used beside conventional accelerometers to record the oscillations. The results show that deviations from optimal coupling to the ground result in significant changes of the dynamic behavior.